Antibiotics and antibiotic resistant genes (ARGs) in groundwater: A global review on dissemination, sources, interactions, environmental and human health risks. (15th December 2020) - Zainab, Syeda Maria; Junaid, Muhammad; Xu, Nan; Malik, Riffat Naseem
HIGHLIGHTS: Global groundwater occurrence of antibiotics and antibiotic resistance genes reviewed. Quinolones, sulfonamides, tetracycline and their genes most prevalent in groundwater. Targeted groundwater antibiotics not proven to pose human health risks. Significant correlations exhibit among antibiotics, bacterial communities, environmental factors, and ARGs. Groundwater is an important environment to investigate the spread and transport of antibiotics and ARGs. Abstract: The discovery and evolution of antibiotics for humans and animals are among the most significant milestones of the 20th century. However, antibiotics play a significant role in the induction and dissemination of antibiotic resistance genes (ARGs) in groundwater that has recently become the primary environmental concern. They are administrated to humans and animals on a large scale and are persistent in the environment. Long term impacts of antibiotics in the ecological environment are not still clearly understood, and their occurrence and consequences have become an important research topic worldwide. The hotspot reservoirs of antibiotics and ARGs include medical facilities, livestock farming, aquaculture, landfills, on-site sanitation systems, sewage, and wastewater treatment plants. Our meta-analysis demonstrated that antibiotics, including ciprofloxacin, sulfamethoxazole, erythromycin, and tetracycline were found at high concentrations while sulfonamide and tetracycline ARGs were more prevalent in groundwater. Moreover, the highest reported concentrations of targeted antibiotics were used to calculate hazard quotient (HQ) and risk quotient (RQ) in global groundwater bodies to estimate environmental and human health risks, respectively. Due to limited available ecotoxicity data, RQ and HQ can only be calculated for a few antibiotics in groundwater. The risk assessment of antibiotics demonstrated that antibiotics with their current groundwater levels pose no human health risks, whereas only ciprofloxacin, erythromycin, flumequine, and sulfamethoxazole revealed moderate to low risks to aquatic species. The occurrence of ARGs and antibiotic resistant bacteria (ARBs) in groundwater is also not likely to pose human health risk but consumption of groundwater contaminated with ARGs and ARBs might contribute to the development of antibiotic resistance in humans. The present review also sheds light on the relationship between ARGs, antibiotics, microbial communities, and environmental factors in groundwater, and reported a significant correlation between them. It also addresses prospects for future outlooks into further areas of relevant research. Graphical abstract: Image, graphical abstract